Unveiling the Inhibitory Potentials of Peptidomimetic Azanitriles and Pyridyl Esters towards SARS-CoV-2 Main Protease: A Molecular Modelling Investigation - Aganze G. Mushebenge; Samuel C. Ugbaja; Sphamandla E. Mtambo; Thandokuhle Ntombela; Joy I. Metu; Oludotun Babayemi; Joy I. Chima; Patrick Appiah-Kubi; Adeshina I. Odugbemi; Mthobisi L. Ntuli; Rene Khan; Hezekiel M. Kumalo (Molecules, 2023)
The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is responsible for COVID-19, which was declared a global pandemic in March 2020 by the World Health Organization (WHO). Since SARS-CoV-2 main protease plays an essential role in the virus’s life cycle, the design of small drug molecules with lower molecular weight has been a promising development targeting its inhibition. Herein, we evaluated the novel peptidomimetic azatripeptide and azatetrapeptide nitriles against SARS-CoV-2 main protease. We employed molecular dynamics (MD) simulations to elucidate the selected compounds’ binding free energy profiles against SARS-CoV-2 and further unveil the residues responsible for the drug-binding properties. Compound 8 exhibited the highest binding free energy of −49.37 ± 0.15 kcal/mol, followed by compound 7 (−39.83 ± 0.19 kcal/mol), while compound 17 showed the lowest binding free energy (−23.54 ± 0.19 kcal/mol). In addition, the absorption, distribution, metabolism, and excretion (ADME) assessment was performed and revealed that only compound 17 met the drug-likeness parameters and exhibited high pharmacokinetics to inhibit CYP1A2, CYP2C19, and CYP2C9 with better absorption potential and blood-brain barrier permeability (BBB) index. The additional intermolecular evaluations suggested compound 8 as a promising drug candidate for inhibiting SARS-CoV-2 Mpro. The substitution of isopropane in compound 7 with an aromatic benzene ring in compound 8 significantly enhanced the drug’s ability to bind better at the active site of the SARS-CoV-2 Mpro.